Prevention of Empty Clusters and Incomplete Data Problems using Modified K-Means and Gaussian Mixture Model - Saha, Sanjib (International Journal of Computer Sciences and Engineering, 2026)
Cluster analysis, in unsupervised learning, divides similar data into groups or clusters that are meaningful and useful. Due to good performance in clustering on massive data sets K-Means clustering is feasible in multiple areas of science and technology. The clustering algorithms may face problems of empty clusters and incomplete data. This empty cluster problem is caused by bad initialization of the center point and this may route to signifying performance degradation. In this theme, the K- Means clustering algorithm is revisited from the probabilistic viewpoint and reformed by the similarity among the K-Means and finite Gaussian Mixture Model (GMM). The initial centroids or current best estimate for the parameters are calculated from the list of all data, known and unknown. Therefore, any two or more primal centroids may not be equal or not very close to each other and data will be assigned to the appropriate clusters with closely fair centroids. The newly proposed modified K-Means using GMM of the Expectation Maximization approach efficiently eliminate the empty cluster and incomplete data problems